Analisis Kelayakan Bisnis Usaha Bercukur Barbershop di Binagriya Pekalongan - Zaki Akhmad Hanif; Abadi, Muhammad Taufiq (CV. Kalimasada Group, 2023)
Hair neatness is one thing that needs attention. It is commonplace that many haircut services are established in various places. In writing this article discusses the barbershop business called Bercuma Barbershop. Bercuma Barbershop is a privately owned barbershop that was developed with the current situation in mind. To start this business, you need a strategic location. The location is located on the edge of the Binagriya highway in the city of Pekalongan. The main purpose of making a business feasibility study analysis report from this barbershop is to make a decision whether or not this business is feasible. In this study using a qualitative approach to the type of field research (field research). Data collection for this method is an interview method by interviewing a barbershop entrepreneur owner, overall the concept is the same from articles or research related to previous barbershop businesses, only there are a few differences but that is not significant. The results of the research show that the Barbershop Shaving business is feasible to be implemented and developed.